Pemahaman Konsep Sistem Koloid Hasil Pembelajaran Menggunakan Metode Diskusi Berbantuan LKS Pada Siswa Kelas XI SMA Negeri 1 Manuhing Tahun Ajaran 2017/2018 - Awi Awi; Ruli Meiliawati; Sri Wahyutami (FKIP Universitas Palangka Raya, 2020)
Discussion is a learning method using scientific conversation by several people who are joined in a group to exchange opinions about a problem topic, or together looking for enumeration to get answers and the truth of a problem. The purpose of this study is to describe the understanding of the colloidal system concept of learning outcomes using the LKS-assisted discussion method in class XI-IPA 1 Manuhing High School Academic Year 2017/2018. This research is descriptive research. The subjects of this study were students of class XI IPA-2 of SMA Negeri 1 Manuhing, totaling 30 students. The instrument used was in the form of concept comprehension test questions (pretest and posttest) in the form of essays for 3 questions, learning achievement sheet, student activity observation sheet and student response questionnaire. Concept understanding data were obtained from written test results in the form of essays given before and after learning using the LKS-assisted discussion method. The results showed an understanding of students' concepts in class XI IPA of SMA Negeri 1 Manuhing in the academic year 2017/2018 about the colloidal system after learning using discussion methods assisted by LKS with an average of 81.5. Changes in the understanding of students' concepts in each concept after learning using the LKS-assisted discussion method, namely: (1) Explaining the difference in coarse suspension, true solution and colloids by 2.96% to 77.03%; (2) Explain the types of colloids based on dispersed phases and dispersing phases by 4.44% to 69.62%; (3) Explain the properties of colloids (tyndall effect, brown motion) by 25% to 100%.